Analisis Kualitas Pelayanan Terhadap Kepuasan Pasien Rawat Jalan Puskesmas (Pusat Kesehatan Masyarakat) Tanjung Palas Kabupaten Bulungan, Kalimantan Utara - Chisillia, Eva; Muazansyah, Imam (JPAP: Jurnal Penelitian Administrasi Publik, 2018)
This study aims to analyze the quality of care for patient satisfaction outpatient puskesmas (Community Health Center) in Tanjung Palas, Bulungan Regency, North Kalimantan. This study uses a quantitative approach. Data collection was carried out by distributing questionnaires to 99 respondents who were outpatients at health centers in Tanjung Palas, Bulungan Regency, North Kalimantan. The data analysis technique used is multiple linear regression analysis. The results of this study indicate that the quality of services that include physical evidence, reliability, responsiveness, assurance, and empathy affect the Outpatient Satisfaction in Tanjung Palas Public Health Center, Bulungan Regency in a positive direction, where the relationship is proven that service quality has a significant effect on outpatient satisfaction at Tanjung Palas Health Center, Bulungan Regency, North Kalimantan with a significance value of less than 0.05.Keywords: Service Quality, Patient Satisfaction, Importance and Performance Analysis